Zaznavanje in pojmi: temelji realistične estetike - Potrč, Matjaž (Časopis za kritiko znanosti, 1999)
The debate on the relationship between perception and notions forms the basis of any type of realist aesthetics. Nevertheless, the fact remains that due to deeply rooted prejudice as a result of our notional apparatus, this relationship is usually misunderstood. For this reason, it is necessary to start from the true ontological nature of the World, understood as One World in terms of Parmenidian materialism. To this, we must add a definition according to which Unity is closely connected with dynamism, since dynamism necessarily entails association.Similarities between the Truth of Profound Ontology and the state of the mind should not be sought on the notional level but in the background of cognition or in the morphological content. Examples from aesthetic activities (painting, music) reveal the profound Ontological Truth of the World and the world's multiple points of departure and dynamism. The True Ontology of the World and perception are closely related. Nevertheless, this does not apply to discreet or divisional notions and the related Rational Ontology. Examples of the perception continuum validate Parmenidian materialism.
Keywords: aesthetics; estetika; realizem; zaznavanje; pojmi; ontologija; ontology